DEVELOPMENT OF AN IMMERSIVE VIRTUAL REALITY (VR) LEARNING ENVIRONMENT FOR SIMULATING CROSS-CULTURAL BUSINESS COMMUNICATION IN ENGLISH - Titin Jumriah; Nino Tsereteli; Tsehaynesh Negash; Klara Schmidt (Journal International of Lingua and Technology, 2025)
The globalization of commerce demands that graduates possess advanced cross-cultural business communication competence in English, a skill difficult to master using low-fidelity traditional training methods. This study addresses the critical gap by developing an Immersive Virtual Reality (VR) Learning Environment designed to simulate high-stakes cross-cultural business communication scenarios. The primary objective was to validate the pedagogical efficacy of this environment using a novel Multi-Modal VR Communication Assessment Framework. A quasi-experimental, pretest-posttest control group design (N=80) was implemented over an eight-week period, comparing VR training with traditional role-play. The VR prototype integrated AI-driven avatar behaviors and an NLP component for real-time assessment. Results showed a strong causal effect of the VR training on competence gain (F=31.92, p < 0.001), with the VR group achieving a substantial raw gain of 16.8 points, significantly exceeding the control group’s 6.9 points. Crucially, the intervention demonstrated a 25% reduction in communication apprehension (t(78) = 4.85, p < 0.001), coupled with superior gains in Cultural Appropriateness (21.5%). The study concludes that the VR environment is not merely an alternative, but a pedagogical necessity capable of mitigating affective barriers and achieving superior gains in nuanced socio-pragmatic competence, thus providing a new standard for holistic professional training.